A Comparison of the Efficacies of Intravaginal and Oral Misoprostol for Induction of Labor in Term Pregnancy : a Randomized Controlled Trial - Suriyalert, Somkid (Journal of Health Science of Thailand, 2017)
The objective of this randomized controlled analytical study was to compare the efficacies of 50 micrograms intravaginal and 100 micrograms oral misoprostol for induction of labor in term pregnancy. One hundred and fifty term pregnant women were divided into two groups. The first was administered with 50 micrograms intravaginally every 6 hours and the second 100 micrograms orally every 6 hours as needed for induction of labor but not over 8 doses. Repeated doses were given until adequate contraction (3 times in 10 minutes) then continued with amniotomy and oxytocin as appropiate. The main outcome measured was time from induction to vaginal delivery. Statistical analysis was performed by unpaired studentีs t-test, Fisherีs exact test, and Chi square test. Demographic characteristics of the two groups showed no significant differrences. The induction time to vaginal delivery was shorter in the intravaginal group than that of the oral group (909.19 SD 36.81 VS 1,283.34 SD 69.38 minutes). The number and total doses were also less in the intravaginal group than those in the oral group (2.38 SD 0.41 VS 3.85 SD 0.81 times and 120.24 SD 15.33 VS 361.71 SD 31.21 micrograms). The successful rates of induction with single dose and less than 24 hours in the intravaginal group were more than those of the oral group (40.00% VS 24.00% and 62.67% VS 37.33%). There were no differences between the groups with respect to the usage of oxytocin rate, delivery method, neonatal outcomes and amounts of postpartum blood loss. There were no episodes of uterine hyperstimulation in both groups but just only tachysystole in intravaginal group was more than in the oral group without statistical significance. No serious side effects of misoprostol could be observed in both groups. In conclusion, the efficacy of 50 micrograms misoprostol administered intravaginally every 6 hours was higher than that of 100 micrograms administered orally every 6 hours for induction of labor in term pregnancy with shorter time to delivery, requiring less doses and yielding the high successful rate. Fifty micrograms of intravaginal misoprostol every 6 hours can be used as an alternative for induction of labor safely at low cost.